PROSPECTS OF FISHERY AND TOURISM INDUSTRY IN PULAU BANYAK VILLAGE LANGKAT DISTRICT - Helentina Mariance Manullang; Zulkarnain Lubis; R.Sabrina (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
The fisheries development can be integrated with varieties activities in tourism sector. Fisheries tourism is a tourism activity based on fishing activities, such as catching, cultivating, processing, and marketing. Pulau Banyak village is one of the areas in Langkat Regency has fisheries potential that can be integrated with tourism and become a tourist destination. This syudy attempts to explore the profile of tourism activities and develop the product that occur in Pulau Banyak Village. Moreover, a tourism development strategy for Pulau Banyak Village can be formulated. The research was conducted using qualitative descriptive methods. The development strategies was analyzed using SWOT matrix. Data were obtained through observation, interviews, and focused discussions with research respondents. The findings revealed that Pulau Banyak Village as a tourist destination has become a special interest tourism package with a fisheries-themed outbound as the main attraction. It was also supported by the existence of a cultivation pond complex and natural river waters. Fishing tourism products can be developed in Agrotourism Education and Tourist Village Tour packages. The strategy for developing fisheries tourism in Pulau Banyak Village includes; developing thematic and cross-regional based tourism packages, improving the completeness of facilities and accessibility, marketing and promoting attractive and effective tourism products, increasing investment, and strengthening the capacity of tourism managers and existing institutions.